Evaluation of the Diagnostic Accuracy of Exhaled Nitric Oxide as a Marker of Infection and Sepsis in Emergency Department Patients - Kendal Farrar; Jacob L. Haapala; Kirsten A. Dalrymple; Lauren R. O’Keefe; Carter R. Anderson; Russ L. Morris; Michael D. Zwank (Emergency Medicine International)
Conclusions: Exhaled NO measurement combined with vital signs has a high sensitivity for the detection of bacterial infection and sepsis. In a clinical setting, this score would be immediately available at the point of patient triage and would help to direct downstream evaluation and care. Further research is warranted.